RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN MATERIAL SPRAY PAINTING DI PT WOHLRAB INDONESIA - Tumanggor, Ferinando; Silalahi, Mesri (Computer Science and Industrial Engineering, 2023)
PT Wohlrab Indonesia has indeed managed materials well. But in its implementation it takes time, energy, and money. This is because doing inventory calculations takes a long time, because it has to be written down on paper and then inputted in Ms. Excel and stored in the file folder. It also requires writing utensils, paper and other equipment. When viewed from a cost perspective, this process requires quite a lot of money because you have to pay for various writing equipment and others, including employee salaries. The research method used is observation, interviews, analysis, conclusion drawing and then the design method used is the SDLC (System Development Life Cycle) method with the Waterfall model. The purpose of this research is to design a Spray Painting Material Management Information System at PT Wohlrab Indonesia and also to build a spray painting material management information system at PT Wohlrab Indonesia. The results of this study are the need for a spray painting material management system at PT Wohlrab Indonesia, it can be concluded that PT Wohlrab Indonesia's spray painting material management information system is designed to provide convenience to admins in managing spray painting material because it is designed with an easy-to-understand or user friendly interface. can also process data quickly and accurately. PT Wohlrab Indonesia's spray painting material management information system uses web-based programming, developed using the PHP programming language and MySQL database. This system can improve admin performance in managing material data and can reduce errors in making reports, loss of material data because data stored in the database cannot be manipulated by parties who do not have access, even conducting data searches can be done quickly and accurately. Keywords : Information; Management; Materials; Systems.